THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND WORK STRESS ON RESILIENCE MODERATED TURNOVER INTENTION - Sumawati Sitepu; Rina Anindita (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
This research is based on the problem of intention to leave caused by leadership and work stress in the 2020 -2021 period. The purpose of this study was to obtain empirical evidence on the influence of transformational leadership and work stress on the turover intention with resilience as a moderator. The research data analysis SEM using the Smart PLS program. The population is nurses who are members of the inpatient installation of 110 personnel, and the sample uses a saturated sample which makes 110 nurses as respondents. The results of the analysis conclude that transformational leadership has no effect on work stress and turnover intentions, work stress has a positive effect on turnover intentions, resilience is unable to moderate the relationship of transformational leadership on work stress and the relationship of work stress on turnover intention.